Semantic function analysis of russian affixes (Eurasian Journal of Philology Science and Education, 2022)
Word-formation motivation is a typical phenomenon for the Russian language. From a synchronic point of view аffixes affect both the semantic composition of the vocabulary and its syntactic structure. In accordance with the principle of composition, the meaning of a derivative word should be made up of the meanings of the affix and the root, that is, the simplest semantic model is exclusively addition in nature: the meaning of the derivative is made up directly from the meanings of the affix and the root without any changes in meaning. Analyzes have shown that the meaning of affixes, roots and derived words is generally quite autonomous; changing any of these elements can lead to a situation where the value of the roots and affixes put together in a synchronous slice does not correspond to the value of the derivative. This article provides an in-depth analysis of the types of semantic functions of affixes in derivational links, these functions include a function of pure grammatical meaning, a dual function of grammatical and lexical meaning, a function of purely lexical meaning and a purely structural-semantic function. The article also discusses the phenomena of synonymy and polysemy of affixes in the Russian language. Since affixes do not have their own nominative function, the realization of their synonymy and polysemy can occur when they are connected with roots. The meanings of polysemous prefixes can coexist, their ability to attach to words is associated with the specific lexical meaning of these words; in real communication, the specific implementation of the prefix’s meaning is sometimes completely determined by the context. Key words: affix, significance, semantic function, synonymy, polysemy